O-023 Pediatric versus adult AVM angioarchitecture: are children really just small adults?. (4th July 2012) - Hetts, S; Kim, H; Cooke, D; English, J; Gupta, N; Stout, C; Kim, W; Dowd, C; Halbach, V; Higashida, R; Lawton, M; Young, W
Abstract : Background and Purpose: Children with brain AVMs are more likely than adults to present with hemorrhage. Prior studies have also demonstrated that AVMs in children are more frequently located deep within the brain than in adults. We sought to determine in greater detail which angioarchitectural features differ between children and adults with brain AVMs. Methods: Under an IRB approved protocol, an institutional brain AVM database collected prospectively since 2001 was queried. Only patients with nidal AVMs were included for analysis; those with vein of Galen malformations, dural AV fistulas, or non-Galenic pial AV fistulas were excluded. Demographic and angioarchitecture information was abstracted and analyzed with Cox univariate and multivariable models. Results: Children were more likely to present with AVM hemorrhage than adults (Abstract O-023 table 1 ). There was an over-representation of Hispanic children as compared to adults when patients were identified by self-reported or parent-reported ethnicity. Although the size of AVM nidus did not differ significantly between children and adults, the location and venous drainage did differ (Abstract O-023 table 2 ). Several angioarchitectural features did not differ significantly in their frequency between children and adults, including: AVM side, cerebellar hemispheric location, presence of arterial aneurysms not related to shunt flow, dural arterial supply, pial to pial arterial collaterialization, moyamoya-like changes, sharp vs diffuse AVM nidal border, nidal aneurysms, number of draining veins, and venous sinus thrombosis. There were non-significant trends toward increasing venous stenosis (p=0.061) and venous reflux (p=0.084) being more frequent in adults as compared to children. Children were more likely to have exclusively deep venous drainage than adults (p<0.001). Concomitantly, whereas children more often harbored deeply-located AVMs, adults more frequently had lobar AVMs. Venous ectasia and flow-related feeding artery aneurysms were more prevalent in adults (p<0.001 and p=0.002, respectively), suggesting that these features may take time to develop and, thus, be underrepresented in children. Conclusions: Although children with brain AVMs were more likely to come to clinical attention due to hemorrhage than their adult counterparts at our institution, high risk features such as venous stenosis and feeding artery aneurysms were underrepresented in those children. AVMs and their draining veins were also more likely to be located deep within the brain in children, raising the possibility that centrally-located AVMs may arise earlier in development or be more likely to come to clinical attention early in life. Competing interests: S Hetts: Silk Road Medical. H Kim: None. D Cooke: None. J English: Silk Road Medical. N Gupta: None. C Stout: None. W Kim: None. C Dowd: None. V Halbach: None. R Higashida: None. M Lawton: None. W Young: None.